ECONOMICS OF PHYSIC NUT (Jatropha curcas L) AS INFLUENCED BY PROPAGATION METHODS, NITROGEN LEVELS AND WEED CONTROL AT SAMARU, NIGERIA. - Emeghara, U. U.; Balogun, O. S.; Alabi, O. F. (FUDMA JOURNAL OF SCIENCES, 2023)
The effect of propagation methods, level of nitrogen application and weed control methods on profitability of Jatropha curcas was examined using Gross margin analysis. Field trials were conducted during the 2008, 2009, 2010 and 2011 farming seasons at the Institute for Agricultural Research (I.A.R) research farm Samaru (11o 111 N; 07o 381 E and 686m above sea level) to compare the economic benefit of propagation methods, level of nitrogen application and weed control methods on growth of Physic Nut using Gross margin analysis. The treatments consisted of two propagation methods of seeds and stem cuttings, four weed control treatments (Fusilade plus Diuron at 1.0 + 0.8 kg a.i ha-1, applied at 4 and 12 weeks after transplanting (WAT), followed by supplementary hoe-weeding at 16 WAT; Atrazine plus Diuron at 1.0 + 0.8 kg a.i ha- 1,, applied at 4 and 12 WAT, followed by supplementary hoe-weeding at 16 WAT; hoe weeded at 4,8,12 and16 WAT and a weedy check) and three levels of nitrogen ( 0, 50 and 100kg ha-1). The treatments were laid out in a split-plot design and replicated three times. Nitrogen levels and weed control treatments were assigned to main plots while the propagation methods were assigned to the sub plots. The results indicated that the highest gross margin of N34, 386.08k was obtained by propagating physic nut through stem cuttings at a combinations of 100kg Nha-1 and postemergence application of Atrazine plus Diuron at 1.0 + 0.8 kg a.i. ha-1, followed by supplementary hoe weeding.
Keywords: Economics, physic nut, propagation methods, Nitrogen levels and weed control